The Development of Nursing Diagnosis-based Indonesian Nursing Diagnosis Standard on Clinical Clinical Pathway among Patients with Stroke Infarction - Hani Riska Ariyanti; Nursalam Nursalam; Slamet Riyadi Yuwono (Alta Dharma Publisher, 2020)
Infarction stroke is a significant health issue in developing countries and developed countries. The purpose of this study was to create a nursing diagnosis based on the Indonesian nursing diagnosis standard on clinical pathway clients with infarction stroke. The research design used to research and develop using a descriptive approach. The sample of this research was the clinical pathway toward the client with infarction stroke and their medical records through medical records search. The development of clinical pathways developed by researchers is the clinical pathway instrument with four nursing diagnoses based on Indonesian nursing diagnosis standards such as impaired physical mobility, risk of falls, impaired verbal communication, and the risk of ineffective cerebral perfusion. The majority (93%) of nursing diagnoses that arise are disorders of physical mobility. Determination of appropriate nursing diagnosis in clinical pathway clients with infarction stroke is essential as a guideline in performing nursing care to the clients, especially for a nurse. Consequently, the nurse can perform nursing care based on nursing care standards.